2022
DOI: 10.1109/tbme.2021.3088218
|View full text |Cite
|
Sign up to set email alerts
|

Robust R-Peak Detection in Low-Quality Holter ECGs Using 1D Convolutional Neural Network

Abstract: Noise and low quality of ECG signals acquired from Holter or wearable devices deteriorate the accuracy and robustness of R-peak detection algorithms. This paper presents a generic and robust system for R-peak detection in Holter ECG signals. While many proposed algorithms have successfully addressed the problem of ECG Rpeak detection, there is still a notable gap in the performance of these detectors on such low-quality ECG records. Methods: In this study, a novel implementation of the 1D Convolutional Neural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…With the aid of the proposed uncertainty quantification method, the QRS-complex location performances of PN-QRS have been close to the limit on the dynamic multi-lead ECG databases. For MIT-BIH, the F 1 score achieves 99.95%, which has exceeded the limits of the current R-peak location methods (99.86% in [43], 99.83% in [44] and 99.91% in [5]) in this database. Similarly, the cumulative errors, FPs and FNs, are only 15 and 9 for PN-QRS evaluated in INCART, approximating the limit of the QRS-complex location performance in this database.…”
Section: Resultsmentioning
confidence: 58%
“…With the aid of the proposed uncertainty quantification method, the QRS-complex location performances of PN-QRS have been close to the limit on the dynamic multi-lead ECG databases. For MIT-BIH, the F 1 score achieves 99.95%, which has exceeded the limits of the current R-peak location methods (99.86% in [43], 99.83% in [44] and 99.91% in [5]) in this database. Similarly, the cumulative errors, FPs and FNs, are only 15 and 9 for PN-QRS evaluated in INCART, approximating the limit of the QRS-complex location performance in this database.…”
Section: Resultsmentioning
confidence: 58%
“…We found that arrhythmia beats (S and V beats) are far less frequent than the normal beats in the MIT-BIH dataset. As described in [5], we generated augmented arrhythmic rhythms from the 20-second ECG segments containing one or more arrhythmia beats by adding baseline wander and motion artifacts from the Noise Stress Test Database [55].…”
Section: Data Augmentationmentioning
confidence: 99%
“…Additionally, we intend to expand our research on arrhythmia classification and its generalization to Holter ECGs with low-quality ECG records. In a recent study [64] we showed that the performance of R peak detection drastically decreases when algorithms that are developed for clean ECG signals are applied to noisy and lowquality Holter ECG data. For this purpose, we are planning to use the China Physiological Signal Challenge (2020) database (CPSC-DB) [65], [66], the largest Holter ECG database which contains more than one million beats.…”
Section: E Computational Complexity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased vector is then fed into an optimized neural network as a train input. The previous studies Zahid et al [15] [16] in 2019, the goal of this research is to create a real-time and accurate QRS complex detector using a new method based on the Bayesian framework. To detect QRS complexes, we present a new technique consisting of two stages: variance-based detection (VBD) and maximum-likelihood estimation (MLE).…”
Section: Introductionmentioning
confidence: 99%